2021
DOI: 10.3390/math9020126
|View full text |Cite
|
Sign up to set email alerts
|

Option Pricing under Double Heston Jump-Diffusion Model with Approximative Fractional Stochastic Volatility

Abstract: Based on the present studies about the application of approximative fractional Brownian motion in the European option pricing models, our goal in the article is that we adopt the creative model by adding approximative fractional stochastic volatility to double Heston model with jumps since approximative fractional Brownian motion is more proper for application than Brownian motion in building option pricing models based on financial market data. We are the first to adopt the creative model. We derive the prici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, Approximation Fractional Brownian motion [27] emerged as a viable alternative, and Thao [27] demonstrated that it constitutes a semimartingale. This has led to increased interest in fractional stochastic volatility models among experts and academics [11], with many researchers incorporating Approximation Fractional Brownian motion in constructing stochastic volatility models [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Approximation Fractional Brownian motion [27] emerged as a viable alternative, and Thao [27] demonstrated that it constitutes a semimartingale. This has led to increased interest in fractional stochastic volatility models among experts and academics [11], with many researchers incorporating Approximation Fractional Brownian motion in constructing stochastic volatility models [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the formula has made many assumptions in advance, for example, the volatility and interest rate of options are assumed to be a constant; the underlying asset follow geometric Brownian motion, etc., is not completely consistent with the actual market situation; thus, the option price calculated by the formula is far from the actual situation. Later, many scholars made corresponding improvements to the model, such as adjusting the time course of the evolution of the underlying asset price, and the interest rate and volatility were subject to a random process [2][3][4][5][6][7][8][9][10][11][12][13][14][15] so as to establish option pricing models closer to the actual situation, such as the CIR model [16,17] and Heston model [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of several more recent research studies have proposed a number of GFBM extensions and adjustments, including the fractional Brownian motion model with adaptive parameters [68], irrational fractional Brownian motion model [69], fractional Brownian motion with two-variable Hurst exponent [70], or approximate fractional Brownian motion [71].…”
Section: Introductionmentioning
confidence: 99%